Upregulation of TLR4-Dependent ATP Production Is Critical for Glaesserella parasuis LPS-Mediated Inflammation - Fei Liu; Yidan Gao; Jian Jiao; Yuyu Zhang; Jianda Li; Luogang Ding; Lin Zhang; Zhi Chen; Xiangbin Song; Guiwen Yang; Jiang Yu; Jiaqiang Wu (Cells, 2023)
Glaesserella parasuis (G. parasuis), an important pathogenic bacterium, cause Glässer’s disease, and has resulted in tremendous economic losses to the global swine industry. G. parasuis infection causes typical acute systemic inflammation. However, the molecular details of how the host modulates the acute inflammatory response induced by G. parasuis are largely unknown. In this study, we found that G. parasuis LZ and LPS both enhanced the mortality of PAM cells, and at the same time, the level of ATP was enhanced. LPS treatment significantly increased the expressions of IL-1β, P2X7R, NLRP3, NF-κB, p-NF-κB, and GSDMD, leading to pyroptosis. Furthermore, these proteins’ expression was enhanced following extracellular ATP further stimulation. When reduced the production of P2X7R, NF-κB-NLRP3-GSDMS inflammasome signaling pathway was inhibited, and the mortality of cells was reduced. MCC950 treatment repressed the formation of inflammasome and reduced mortality. Further exploration found that the knockdown of TLR4 significantly reduced ATP content and cell mortality, and inhibited the expression of p-NF-κB and NLRP3. These findings suggested upregulation of TLR4-dependent ATP production is critical for G. parasuis LPS-mediated inflammation, provided new insights into the molecular pathways underlying the inflammatory response induced by G. parasuis, and offered a fresh perspective on therapeutic strategies.